In Vitro Study of Piper Crocatum Ruiz & Pav Potency as HMG-CoA Reductase and Malondialdehyde Formation Inhibitor - Zaelani, Bella Fatima Dora; Safithri, Mega; Andrianto, Dimas (Indonesian Journal of Applied Research (IJAR), 2024)
Coronary heart disease is a serious health problem and it is known to be lethal. The disease can be triggered by the accumulation of cholesterol plaques in the walls of blood vessels This cholesterol formation is assisted by methylglutaril-CoA reductase (HMG-CoA reductase) enzyme. Red betel contains active compounds that have the potential to act as HMG-CoA reductase inhibitor. This study aimed to predict the potential of ethanol extract compounds, water fraction, ethyl acetate fraction, and red betel n-hexane fraction as HMG-CoA reductase inhibitors by in vitro method. The in vitro method which consisted of extraction by maceration, graded fractionation with n-hexane, ethyl acetate, and water, continued by thiobarbituric acid (TBA) method to see the potential antioxidant activity of the sample. The Result showed that the highest inhibition of HMG-CoA reductase is 94% was found in the concentration 200 ppm ethyl acetate fraction. Also antioxidant activity of red betel showed by the inhibition of malondialdehyde formation had the highest activity in the ethyl acetate fraction than other fractions used.